Water permeable brick based on fly ash-based geopolymer artificial aggregate and preparation method thereof

By controlling the use of liquid sodium silicate and inorganic retarder, the fluidity and settling time of the mixture are regulated, and fly ash is sprayed on the surface of the aggregate to form a buffer layer, the problem of low fly ash utilization rate and difficult to take into account both the strength and permeability of permeable bricks is solved, and the efficient utilization of fly ash is achieved and high-performance permeable bricks are prepared.

CN119822693APending Publication Date: 2025-04-15ZHEJIANG TIANDI ENVIRONMENTAL PROTECTION TECH CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411951160.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In the prior art, fly ash utilization rate is low, and the strength and permeability of permeable bricks are difficult to take into account. The bonding force between the aggregate and the matrix interface is insufficient, resulting in poor mechanical properties and durability of permeable bricks.

Method used

By controlling the use of low-modulus liquid sodium silicate and inorganic retarder, the fluidity and coagulation time of the mixture are regulated, the difficulty of aggregate forming construction is significantly reduced, the strength of aggregate is improved, and the strength, fly ash is formed by spraying fly ash on the surface of the aggregate to form a "fly ash buffer layer", which improves the strength, durability and wear resistance of permeable bricks.

Benefits of technology

The efficient utilization of large amounts of fly ash was achieved, and permeable bricks with high strength, high water permeability and good durability were prepared, which reduced production energy consumption and improved the utilization rate of fly ash.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a water permeable brick based on fly ash-based geopolymer artificial aggregate and a preparation method thereof. By controlling the use of the low-modulus liquid sodium silicate and the inorganic retarder and regulating and controlling the flowability and the setting time of the mixture, the forming construction difficulty of the aggregate is remarkably reduced, the strength of the aggregate is improved, and the large-volume fly ash-based geopolymer artificial aggregate is prepared; the fly ash is sprayed on the surface of the aggregate to form a fly ash buffer layer, so that the strength, durability and wear resistance of the water permeable brick are remarkably improved. According to the invention, the large-dosage fly ash provides a sufficient silicon source in the forming process of the geopolymer artificial aggregate, and the fly ash fine particles fill gaps between the geopolymer artificial aggregate and the geopolymer slurry in the pressing process of the water permeable brick, so that the overall compactness of the mixture is enhanced, and meanwhile, the resource utilization rate of the fly ash is greatly improved; and the problem of high-efficiency utilization of high-volume fly ash in the water-permeable brick is solved, and the water-permeable brick has remarkable social, economic and ecological environmental benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of permeable bricks and preparation thereof, and in particular to a permeable brick based on fly ash-based polymer artificial aggregate and a preparation method thereof. Background Art

[0002] As solid waste from coal-fired power plants, fly ash has a huge annual output. Its random stacking will cause serious land occupation, environmental pollution and waste of resources. Although some fly ash can be used as an admixture for cement, its utilization rate is still low, especially the application of low-activity fly ash (such as Class F fly ash, CaO content <10%) is limited, resulting in large-scale stockpiling, exacerbating environmental problems. At the same time, with the advancement of sponge city construction, the demand for permeable bricks with good permeability and mechanical properties is growing. In the prior art, the preparation methods of permeable bricks mainly include high-temperature sintering method, cement concrete method and geopolymer concrete method. Although the high-temperature sintering method can prepare permeable bricks with good permeability and high strength, it has high energy consumption and high production cost; the cement concrete method has relatively low energy consumption, but low permeability and strength, and the fly ash consumption is not high; the geopolymer concrete method can consume a large amount of fly ash, but the permeability and strength are generally low. Although the existing technologies (such as CN113292313 A, CN 111978096 A, CN 110606720 B) also attempt to use fly ash to prepare permeable bricks, there are some shortcomings: for example, the high-temperature sintering process consumes huge energy and is not conducive to environmental protection; or it is difficult to take both the permeability coefficient and strength into account, and the permeability or strength index does not reach the ideal level; or the utilization rate of fly ash is not high. These methods have failed to effectively solve the problem of efficient utilization of low-activity fly ash (Class F fly ash) and the preparation of high-strength, high-permeability permeable bricks. In particular, the utilization rate of Class F fly ash in the existing technology is low, which limits the application scope and performance improvement of geopolymer materials. In addition, the existing technology pays little attention to the improvement of the interface bonding force between aggregates and matrix materials and the overall density, which affects the mechanical properties and durability of permeable bricks. Therefore, there is an urgent need for a new preparation method that can efficiently utilize large amounts of fly ash, especially low-activity Class F fly ash, to prepare permeable bricks with high strength, high permeability and good durability, and reduce production energy consumption. Summary of the invention

[0003] The present invention aims to solve the problems in the prior art such as low fly ash utilization rate, difficulty in balancing the strength and permeability of permeable bricks, and insufficient bonding force between aggregate and matrix interfaces, and provides a high-dosage fly ash-based permeable brick. By controlling the use of low-modulus liquid sodium silicate (water glass) and inorganic retarders, the fluidity and setting time of the mixture are regulated, the difficulty of aggregate molding construction is significantly reduced, the strength of the aggregate is improved (compressive strength exceeds 68MPa), and by spraying fly ash on the surface of the aggregate to form a "fly ash buffer layer", the strength, durability and wear resistance of the permeable brick are significantly improved, thereby achieving efficient utilization of low-activity fly ash and preparation of high-performance permeable bricks.

[0004] Another object of the present invention is to provide a method for preparing a large amount of fly ash-based polymer artificial aggregate, by controlling the use of low modulus liquid sodium silicate (water glass) and inorganic retarder, regulating the fluidity and setting time of the mixture, significantly reducing the difficulty of aggregate molding construction, and improving the strength of the large amount of fly ash-based polymer artificial aggregate (compressive strength exceeds 68MPa).

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] The present invention provides a method for preparing a permeable brick based on fly ash-based polymer artificial aggregate, comprising the following steps:

[0007] (1) Preparation of fly ash-based polymer artificial aggregate with large dosage:

[0008] (1-1) Ingredients: including powder ingredients and liquid ingredients;

[0009] The powder ingredients are: fly ash and granulated blast furnace slag are weighed according to a weight ratio, wherein the fly ash content is 70-90%, and the granulated blast furnace slag content is 10-30%, and the powder materials are mixed evenly;

[0010] The liquid ingredients include: weighing water, water glass and inorganic retarder according to weight ratio, wherein the water content is 15-30%, the water glass content is 60-85%; the inorganic retarder content is 0.5-2%, and the liquid materials are mixed evenly;

[0011] (1-2) Slurry preparation: Mix the powder material and the liquid material, stir for 5-15 minutes, and prepare a uniform slurry; the mass ratio of the powder material to the liquid material is 1.5:1-3:1;

[0012] (1-3) Molding: Pour the slurry into the mold and vibrate for 5-10 seconds to make it dense;

[0013] (1-4) Curing: After the slurry initially sets, steam curing or autoclave curing is used;

[0014] (1-5) Processing: After curing, the solidified body is crushed and sieved by a sieving device to obtain fly ash-based polymer artificial aggregate with a particle size of 2-5 mm and 5-10 mm;

[0015] (2) mixing: the fly ash-based polymer artificial aggregate prepared in step (1) is mixed and stirred evenly with a geopolymer slurry at a mass ratio of 3:1-5:1 until all surfaces of the fly ash-based polymer artificial aggregate are coated with the geopolymer slurry to obtain a mixture;

[0016] (3) Surface treatment: Spray fly ash on the surface of the mixture obtained in step (2), with the spraying amount being 0.5% to 2% of the total mass of the geopolymer slurry and the artificial aggregate, and continue stirring to make the fly ash evenly coated on the surface of the artificial aggregate coated with the geopolymer slurry to form a fly ash buffer layer, thereby obtaining a mixture;

[0017] (4) Molding: Filling the mixture obtained in step (3) into a mold, applying a pressure of 8-10 MPa to press and mold to obtain a brick;

[0018] (5) Curing: Curing the bricks obtained in step (4) by steam curing or autoclave curing.

[0019] Preferably, the geopolymer slurry is prepared from water glass and fly ash, wherein the mass ratio of fly ash to water glass is 60-75:25-40; the water glass modulus is 1.2-1.5, the solid content is 45%-65%, and the fluidity of the slurry is 180-220 mm.

[0020] Preferably, the fly ash-based polymer artificial aggregate in step (2) is prepared by mixing two fly ash-based polymer artificial aggregates of two particle sizes, 2-5 mm and 5-10 mm, in a mass ratio of 8:2 to 4:6.

[0021] Preferably, the granulated blast furnace slag has an activity index of >95%, a particle size of 25-300 μm, and a calcium oxide content of ≥40%; the fly ash has an activity index of ≥50%, a particle size of 25-300 μm, and an aluminum oxide content of ≥30%; more preferably, the fly ash has an activity index of 50-80%. The method of the present invention is applicable to low-activity fly ash (e.g., Class F fly ash).

[0022] Preferably, the modulus of the water glass solution in step (1-1) is 1.3-1.5, and the solid content is 20-30%.

[0023] Preferably, the inorganic retarder is one or both of barium chloride and barium nitrate.

[0024] Preferably, the initial setting time of the slurry in step (1-2) is 30-90 minutes.

[0025] The present invention also provides a permeable brick based on fly ash-based polymer artificial aggregate, which is prepared by the preparation method of the permeable brick based on fly ash-based polymer artificial aggregate.

[0026] The present invention also provides a method for preparing a large amount of fly ash-based polymer artificial aggregate, comprising the following steps:

[0027] (1-1) Ingredients: including powder ingredients and liquid ingredients;

[0028] The powder ingredients are: fly ash and granulated blast furnace slag are weighed according to a weight ratio, wherein the fly ash content is 70-90%, and the granulated blast furnace slag content is 10-30%, and the powder materials are mixed evenly;

[0029] The liquid ingredients are: weigh water, water glass and inorganic retarder according to weight ratio, wherein the water content is 15-30%, the water glass content is 60-85%; the inorganic retarder content is 0.5-2%, and the liquid is mixed evenly;

[0030] (1-2) Slurry preparation: Mix the powder material and the liquid material and stir for 5-15 minutes to prepare a uniform slurry;

[0031] (1-3) Molding: Pour the slurry into the mold and vibrate for 5-10 seconds to make it dense;

[0032] (1-4) Curing: After the slurry initially sets, steam curing or autoclave curing is used;

[0033] (1-5) Processing: After curing, the solidified body is crushed and sieved by screening equipment to obtain fly ash-based polymer artificial aggregate with particle sizes of 2-5 mm and 5-10 mm.

[0034] Preferably, the curing temperature of the steam curing in step (1-4) is 70-100°C, and the time is 24-48 hours; the pressure of the autoclave curing in step (1-4) is 0.6-1.0 MPa, and the time is 6-10 hours; the curing temperature of the steam curing in step (4) is 70-100°C, and the time is 24-48 hours; the pressure of the autoclave curing in step (4) is 0.6-1.0 MPa, and the time is 6-10 hours.

[0035] Specifically, the compressive strength of the fly ash-based polymer artificial aggregate prepared by the present invention is greater than 68 MPa, and the testing method is as follows: the slurry prepared in step (1-2) is formed into a cubic test block of 10 cm×10 cm×10 cm, and after curing according to step (1-4), its compressive strength is tested.

[0036] The present invention adopts geopolymer slurry as the bonding material of geopolymer-based artificial aggregate, adopts inorganic retarder to effectively control the setting time, and the geopolymer slurry significantly enhances the bonding force between the aggregate and the matrix; by spraying fly ash during the molding process to form a buffer layer, the buffer layer fills the gap between the artificial aggregate and the geopolymer, thereby enhancing the overall density of the permeable brick; the above two aspects improve the compressive strength, wear resistance and durability of the permeable brick; the compressive strength of the permeable brick is greater than 33MPa, and the water permeability coefficient is greater than 2.2×10 -2 cm / s, the grinding pit length is less than 26mm, and the efficient utilization of low-activity fly ash is achieved, which has significant economic and environmental benefits.

[0037] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0038] 1. Efficient utilization of fly ash: The present invention can efficiently utilize large amounts of fly ash, and is also suitable for low-activity fly ash (such as Class F fly ash). The fly ash dosage in the preparation process of artificial aggregate and permeable brick is as high as 70-90% and 60-75%, respectively, realizing high value-added resource utilization of industrial waste residues, significantly improving the utilization rate of fly ash, especially improving the utilization rate of low-activity fly ash, reducing environmental pollution and land occupation, and having significant economic and environmental benefits.

[0039] 2. Excellent permeable brick performance: The permeable brick prepared by the present invention has high strength (compressive strength greater than 33MPa) and high permeability (permeability coefficient greater than 2.2×10-2cm / s), as well as good wear resistance (wear pit length less than 26mm). All performance indicators meet or even exceed the requirements of the "Permeable Pavement Bricks and Permeable Road Panels" (GB / T25993 2010) standard, and have broad market application prospects.

[0040] 3. Enhance the interface bonding force and overall density: Use geopolymer slurry to bond artificial aggregate, and spray fly ash on the surface of the mixture to form a buffer layer, which effectively enhances the interface bonding force between aggregate and matrix material, improves the overall density and crack resistance of permeable bricks, thereby improving its mechanical properties and durability.

[0041] 4. Low energy consumption and low cost production: The steam curing or autoclave curing process is adopted to avoid the high energy consumption process of high temperature sintering, significantly reduce the production cost and energy consumption, and realize the low-carbon and environmentally friendly production of permeable bricks.

[0042] 5. Simplified production process: The process flow of the present invention is simple and easy to operate, convenient for large-scale industrial production. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail by examples below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other. Moreover, any equivalent scheme obtained by conventional technical means based on the concept of the present invention belongs to the protection scope of the present invention.

[0044] In the following examples, the granulated blast furnace slag has an activity index of >95%, a particle size of 25-300 μm, and a calcium oxide content of ≥40%; the fly ash is Class F fly ash, with an activity index of 50%-80%, a particle size of 25-300 μm, and an aluminum oxide content of ≥30%.

[0045] In the following examples, the modulus of the water glass solution in step (1) is 1.3-1.5, and the solid content is 20-30%; the initial setting time of the slurry in step (1) is 30-90 minutes.

[0046] Example 1

[0047] The method for preparing the permeable brick based on fly ash-based polymer artificial aggregate of this embodiment comprises the following steps:

[0048] (1) Preparation of fly ash-based polymer artificial aggregate with high content

[0049] Fly ash and granulated blast furnace slag are mixed in a mass ratio of 70:30, and the powder batch is obtained after being mixed evenly; water, water glass and retarder barium chloride are mixed in a mass ratio of 15:84.5:0.5, and the liquid batch is obtained after being stirred and mixed evenly; the powder batch is added to the mixer and then the liquid batch is added, and the mass ratio of powder to liquid is 2:1. Using the mixer, stir slowly for 120 seconds, stop for 15 seconds, and then stir quickly for 120 seconds to obtain a uniform slurry. Pour the slurry into a mold of 10×10×10cm and 50×50×5cm and vibrate for 8 seconds. After the slurry is initially solidified, put the mold into a steam curing box at 80℃ for steam curing for 24 hours; after the steam curing is completed, the solidified body is crushed by a crusher and sieved by a screening device to obtain fly ash-based polymer artificial aggregate with a particle size of 2-5mm and 5-10mm. After testing, the compressive strength of the 10×10×10cm sample prepared this time is 68.5MPa.

[0050] (2) Preparation of permeable bricks with artificial aggregate

[0051] The water glass with a modulus of 1.5 and a solid content of 50% and fly ash are mixed evenly in a mass ratio of 35:65, and the mixture is stirred slowly for 120 seconds, stopped for 15 seconds, and then stirred quickly for 120 seconds using a mixer to prepare a geopolymer slurry with a fluidity of 200 mm. The fly ash-based polymer artificial aggregate with a particle size of 2-5 mm and 5-10 mm obtained in the above (1) is mixed in a mass ratio of 8:2, and then gradually added to the slurry and stirred evenly. The mass ratio of artificial aggregate to slurry is 4:1, until all the surfaces of artificial aggregate are coated with the geopolymer slurry. After spraying fly ash on the surface of the obtained mixture, stirring is continued so that the fly ash is evenly coated on the surface of the artificial aggregate coated with the geopolymer slurry to prepare a mixture. The mass of the sprayed fly ash is 2% of the total mass of the geopolymer slurry and the fly ash-based polymer artificial aggregate. Stirring is continued so that the fly ash is evenly distributed on the surface of the mixture to form a fly ash buffer layer. The obtained mixture was filled into a mold and pressed under a pressure of 8 MPa to obtain a brick blank. The obtained brick blank was steam cured at a temperature of 80°C for 24 hours. Finally, a high-dosage fly ash-based permeable brick was obtained. The relevant performance indicators of the product are shown in Table 1.

[0052] Example 2

[0053] The method for preparing the permeable brick based on fly ash-based polymer artificial aggregate of this embodiment comprises the following steps:

[0054] (1) Preparation of fly ash-based polymer artificial aggregate with high content

[0055] Fly ash and granulated blast furnace slag are mixed in a mass ratio of 75:25, and the powder batch is obtained after being mixed evenly; water, water glass and retarder barium chloride are mixed in a mass ratio of 14.5:85:0.5, and the liquid batch is obtained after being stirred evenly; the powder batch is added to the mixer and then the liquid batch is added, and the mass ratio of powder to liquid is 2.7:1. Using the mixer, stir slowly for 120 seconds, stop for 15 seconds, and then stir quickly for 120 seconds to obtain a uniform slurry. The slurry is poured into a 50cm×50cm×5cm tray and vibrated for 8 seconds. At the same time, 3 10cm×10cm×10cm specimens are also formed for testing compressive strength; after the slurry is initially set, the tray is placed in a steam curing box at a temperature of 90°C and steamed for 48 hours; after the steam curing is completed, the solidified body is crushed by a crusher and sieved by a screening device to obtain fly ash-based polymer artificial aggregates with particle sizes of 2-5mm and 5-10mm. After testing, the compressive strength of the 10cm×10cm×10cm sample is 72.2MPa.

[0056] (2) Preparation of permeable bricks with artificial aggregate

[0057] The water glass with a modulus of 1.5 and a solid content of 50% and fly ash are mixed evenly in a mass ratio of 30:70, and the mixture is stirred slowly for 120 seconds, stopped for 15 seconds, and then stirred quickly for 120 seconds using a mixer to prepare a geopolymer slurry with a fluidity of 200 mm; the fly ash-based polymer artificial aggregate with a particle size of 2-5 mm and 5-10 mm obtained in the above (1) is mixed in a mass ratio of 7:3, and then gradually added to the slurry and stirred evenly, with the mass ratio of artificial aggregate to slurry being 4.5:1, until all the surfaces of the artificial aggregate are coated with the geopolymer slurry; after spraying fly ash on the surface of the obtained mixture, stirring is continued so that the fly ash is evenly coated on the surface of the artificial aggregate coated with the geopolymer slurry to prepare a mixture, and the mass of the sprayed fly ash is 3% of the total mass of the geopolymer slurry and the fly ash-based polymer artificial aggregate; stirring is continued so that the fly ash is evenly distributed on the surface of the mixture to form a fly ash buffer layer. The obtained mixture was filled into a mold and pressed under a pressure of 8 MPa to obtain a brick blank; the obtained brick blank was autoclaved at a pressure of 0.8 MPa for 8 hours. Finally, a high-dosage fly ash-based permeable brick was obtained, and the relevant performance indicators of the product are shown in Table 1.

[0058] Example 3

[0059] The method for preparing the permeable brick based on fly ash-based polymer artificial aggregate of this embodiment comprises the following steps:

[0060] (1) Preparation of fly ash-based polymer artificial aggregate with high content

[0061] Fly ash and granulated blast furnace slag are mixed in a mass ratio of 80:20, and the powder batch is obtained after being mixed evenly; water, water glass and retarder barium nitrate are mixed in a mass ratio of 14:85:1, and the liquid batch is obtained after being stirred evenly; the powder batch is added to the mixer and then the liquid batch is added, and the mass ratio of powder to liquid is 2.3:1. Using the mixer, stir slowly for 120 seconds, stop for 15 seconds, and then stir quickly for 120 seconds to obtain a uniform slurry. The slurry is poured into a 50cm×50cm×5cm tray and vibrated for 8 seconds. At the same time, 3 10cm×10cm×10cm specimens are also formed for testing compressive strength; after the slurry is initially set, the tray is placed in a steam curing box at a temperature of 90℃ and steamed for 48 hours; after the steam curing is completed, the solidified body is crushed by a crusher and sieved by a screening device to obtain fly ash-based polymer artificial aggregates with particle sizes of 2-5mm and 5-10mm. After testing, the compressive strength of the 10cm×10cm×10cm sample is 71.4MPa.

[0062] (2) Preparation of permeable bricks with artificial aggregate

[0063] The water glass with a modulus of 1.5 and a solid content of 50% and fly ash are mixed evenly in a mass ratio of 40:60, and the mixture is stirred slowly for 120 seconds, stopped for 15 seconds, and then stirred quickly for 120 seconds using a mixer to prepare a geopolymer slurry with a fluidity of 200 mm; the fly ash-based polymer artificial aggregate with a particle size of 2-5 mm and 5-10 mm obtained in the above (1) is mixed in a mass ratio of 8:2, and then gradually added to the slurry and stirred evenly, with the mass ratio of artificial aggregate to slurry being 4:1, until all the surfaces of the artificial aggregate are coated with the geopolymer slurry; after spraying fly ash on the surface of the obtained mixture, stirring is continued so that the fly ash is evenly coated on the surface of the artificial aggregate coated with the geopolymer slurry to prepare a mixture, and the mass of the sprayed fly ash is 2% of the total mass of the geopolymer slurry and the fly ash-based polymer artificial aggregate; stirring is continued so that the fly ash is evenly distributed on the surface of the mixture to form a fly ash buffer layer. The obtained mixture was filled into a mold and pressed under a pressure of 10 MPa to obtain a brick blank; the obtained brick blank was steam cured at a temperature of 80°C for 36 hours. Finally, a high-dosage fly ash-based permeable brick was obtained, and the relevant performance indicators of the product are shown in Table 1.

[0064] Example 4

[0065] The method for preparing the permeable brick based on fly ash-based polymer artificial aggregate of this embodiment comprises the following steps:

[0066] (1) Preparation of fly ash-based polymer artificial aggregate with high content

[0067] Fly ash and granulated blast furnace slag are mixed in a mass ratio of 80:20, and the powder batch is obtained after being mixed evenly; water, water glass and retarder (barium chloride and barium nitrate each accounting for 50%) are mixed in a mass ratio of 14.5:84:1.5, and the liquid batch is obtained after being stirred and mixed evenly; the liquid batch is added after the powder batch is added to the mixer, and the mass ratio of powder to liquid is 2.5:1. Using a mixer, stir slowly for 120 seconds, stop for 15 seconds, and then stir quickly for 120 seconds to obtain a uniform slurry; pour the slurry into a 50cm×50cm×5cm tray and vibrate for 8 seconds. At the same time, three 10cm×10cm×10cm specimens are formed to test the compressive strength; after the slurry is initially set, the tray is placed in a steam curing box at a temperature of 80°C and steamed for 24 hours; after the steam curing is completed, the solidified body is mechanically crushed by a crusher and sieved by a screening device to obtain fly ash-based polymer artificial aggregates with particle sizes of 2-5mm and 5-10mm. After testing, the compressive strength of the 10cm×10cm×10cm specimen is 69.6MPa.

[0068] (2) Preparation of permeable bricks with artificial aggregate

[0069] The water glass with a modulus of 1.5 and a solid content of 50% and fly ash are mixed evenly in a mass ratio of 35:65, and the mixture is stirred slowly for 120 seconds, stopped for 15 seconds, and then stirred rapidly for 120 seconds using a mixer to prepare a geopolymer slurry with a fluidity of 200 mm; the fly ash-based polymer artificial aggregate with a particle size of 2-5 mm and 5-10 mm obtained in the above (1) is mixed in a mass ratio of 4:6, and then gradually added to the slurry, with a mass ratio of artificial aggregate to slurry of 5:1, and stirring is continued until all the particles are mixed. The surface of the artificial aggregate is coated with geopolymer slurry; fly ash is sprayed on the surface of the obtained mixture, and the mixture is stirred continuously to make the fly ash evenly coated on the surface of the artificial aggregate coated with the geopolymer slurry to prepare a mixture, and the mass of the sprayed fly ash is 1.5% of the total mass of the geopolymer geopolymer slurry and the fly ash-based polymer artificial aggregate; the obtained mixture is filled into a mold, and a pressure of 9MPa is applied to press and form to obtain a brick; the obtained brick is autoclaved and cured at a pressure of 0.9MPa for 7 hours. Finally, a high-dosage fly ash-based permeable brick is obtained, and the relevant performance indicators of the product are shown in Table 1.

[0070] Comparative Example 1: Using natural aggregate to prepare cement-based permeable bricks without surface treatment of aggregates

[0071] Cement, fly ash and silica fume are mixed evenly at a mass ratio of 55:40:5, water is added at a water-cement ratio of 0.20, and then polycarboxylic acid water reducer is added at 0.8% of the total mass of cement, fly ash and silica fume, and stirred with a mixer to prepare a slurry with a flow of 200mm; 2-5mm and 5-10mm natural aggregates are mixed at a mass ratio of 8:2, and then gradually added to the slurry, stirred evenly, and the mass ratio of aggregate to slurry is 5:1, until the slurry completely covers the artificial aggregate; the obtained mixture is filled into a mold, and a pressure of 9MPa is applied to press and form to obtain a brick; the obtained brick is autoclaved and cured at a pressure of 0.9MPa for 7 hours. The relevant performance indicators of the permeable bricks are finally obtained as shown in Table 1.

[0072] Comparative Example 2: Using fly ash-based polymer artificial aggregate to prepare geopolymer permeable bricks without treating the aggregate surface

[0073] A method for preparing a permeable brick using a polymer artificial aggregate containing a large amount of fly ash and the like, comprising the following steps:

[0074] (1) Preparation of fly ash-based polymer artificial aggregate

[0075] Fly ash and granulated blast furnace slag are mixed in a mass ratio of 80:20, and the powder batch is obtained after being mixed evenly; water, water glass and retarder barium chloride are mixed in a mass ratio of 14.5:84:1.5, and the liquid batch is obtained after being stirred evenly; the powder batch is added to the mixer and then the liquid batch is added, and the mass ratio of powder to liquid is 2.25:1. Using the mixer, stir slowly for 120 seconds, stop for 15 seconds, and then stir quickly for 120 seconds to obtain a uniform slurry. The slurry is poured into a 50cm×50cm×5cm tray and vibrated for 8 seconds. At the same time, 3 10cm×10cm×10cm specimens are also formed for testing compressive strength; after the slurry is initially set, the tray is placed in a steam curing box at a temperature of 80℃ and steamed for 24 hours; after the steam curing is completed, the solidified body is crushed by a crusher and sieved by a screening device to obtain fly ash-based polymer artificial aggregates with particle sizes of 2-5mm and 5-10mm. After testing, the compressive strength of the 10cm×10cm×10cm sample is 69.6MPa.

[0076] (2) Preparation of permeable bricks with artificial aggregate

[0077] Mix water glass with a modulus of 1.5 and a solid content of 50% with fly ash in a mass ratio of 35:65, stir slowly for 120 seconds, stop for 15 seconds, and then stir quickly for 120 seconds to obtain a uniform slurry. Pour the slurry into a mold of 10×10×10cm and 50×50×5cm and vibrate for 8 seconds. After the slurry is initially solidified, put the mold into an 80°C steam curing box for steam curing for 24 hours; after the steam curing is completed, crush the solidified body with a crusher and screen it through a screening device to obtain fly ash-based polymer artificial aggregate with a particle size of 2-5mm and 5-10mm.

[0078] The fly ash-based polymer artificial aggregates with particle sizes of 2-5mm and 5-10mm obtained in (1) above were mixed in a mass ratio of 4:6, and then gradually added to the slurry and stirred evenly, with a mass ratio of artificial aggregate to slurry of 5.5:1, until the slurry completely covered the artificial aggregate; the obtained mixture was filled into a mold, and pressed under a pressure of 9MPa to obtain a brick; the obtained brick was autoclaved at a pressure of 0.9MPa for 7 hours. Finally, a high-dosage fly ash-based permeable brick was obtained, and the relevant performance indicators of the product are shown in Table 1.

[0079] Table 1 Performance indicators of prepared permeable bricks

[0080] Example Compressive strength(MPa) <![CDATA[Coefficient of permeability (×10 -2 cm / s)]]> Grinding pit length (mm) Example 1 33.6 2.34 24.1 Example 2 35.8 2.28 25.3 Example 3 37.3 2.41 23.4 Example 4 34.5 2.23 24.6 Comparative Example 1 32.5 2.24 33.2 Comparative Example 2 33.2 2.19 35.1

[0081] The present invention controls the use of low modulus liquid sodium silicate and inorganic retarder, regulates the fluidity and setting time of the mixture, significantly reduces the difficulty of aggregate molding construction, improves the strength of the aggregate (compressive strength exceeds 68MPa), and forms a "fly ash buffer layer" by spraying fly ash on the surface of the aggregate, which significantly improves the strength, durability and wear resistance of the permeable brick. The large amount of fly ash provides sufficient silicon source in the molding process of geopolymer artificial aggregate, and the fine fly ash particles fill the gap between the geopolymer artificial aggregate and the geopolymer slurry during the pressing process of the permeable brick, thereby enhancing the overall density of the mixture. Through the technical solution of the present invention, the resource utilization rate of fly ash is greatly improved, the environmental hazard problem of the storage yard caused by fly ash is alleviated, the high added value utilization of fly ash is realized, and the problem of efficient utilization of high-dosage fly ash in permeable bricks is solved, which has significant social, economic and ecological environmental benefits.

[0082] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing permeable bricks based on fly ash-based polymer artificial aggregate, characterized in that: The following steps are involved: (1) Preparation of fly ash-based polymer artificial aggregate with large amount of admixture: (1-1) Ingredients: including powder ingredients and liquid ingredients; The powder ingredients are: fly ash and granulated blast furnace slag are weighed according to a weight ratio, wherein the fly ash content is 70-90%, and the granulated blast furnace slag content is 10-30%, and the powder materials are mixed evenly; The liquid ingredients are: weighing water, water glass and inorganic retarder according to weight ratio, wherein the water content is 15-30%, the water glass content is 60-85%, and the inorganic retarder content is 0.5-2%, and the liquid materials are mixed evenly; (1-2) Slurry preparation: Mix the powder material and the liquid material, stir for 5-15 minutes, and prepare a uniform slurry; the mass ratio of the powder material to the liquid material is 1.5:1-3:1; (1-3) Molding: Pour the slurry into the mold and vibrate for 5-10 seconds to make it dense; (1-4) Curing: After the slurry initially sets, steam curing or autoclave curing is used; (1-5) Processing: After curing, the solidified body is crushed and sieved by a sieving device to obtain fly ash-based polymer artificial aggregate with a particle size of 2-5 mm and 5-10 mm; (2) mixing: the fly ash-based polymer artificial aggregate prepared in step (1) is mixed and stirred evenly with a geopolymer slurry at a mass ratio of 3:1-5:1, until all surfaces of the fly ash-based polymer artificial aggregate are coated with the geopolymer slurry to obtain a mixture; (3) Surface treatment: Spray fly ash on the surface of the mixture obtained in step (2), with the spraying amount being 0.5% to 2% of the mass of the geopolymer slurry and the fly ash-based polymer artificial aggregate, and continue stirring to make the fly ash evenly coated on the surface of the fly ash-based polymer artificial aggregate coated with the geopolymer slurry to form a fly ash buffer layer, thereby obtaining a mixture; (4) Molding: Filling the mixture obtained in step (3) into a mold, applying a pressure of 8-10 MPa to press and mold to obtain a brick; (5) Curing: Curing the bricks obtained in step (4) by steam curing or autoclave curing.

2. The method for preparing permeable bricks based on fly ash-based polymer artificial aggregate according to claim 1, characterized in that: The geopolymer slurry in step (2) is prepared from water glass and fly ash, wherein the mass ratio of fly ash to water glass is (60-75):(25-40).

3. The method for preparing permeable bricks based on fly ash-based polymer artificial aggregate according to claim 2, characterized in that: The water glass modulus in step (2) is 1.2-1.5, the solid content is 45%-65%, and the fluidity of the slurry is 180-220 mm.

4. The method for preparing permeable bricks based on fly ash-based polymer artificial aggregate according to claim 1, characterized in that: The fly ash-based polymer artificial aggregate in step (2) is prepared by mixing two fly ash-based polymer artificial aggregates of two particle sizes, 2-5 mm and 5-10 mm, in a mass ratio of 8:2 to 4:

6.

5. The method for preparing permeable bricks based on fly ash-based polymer artificial aggregate according to claim 1, characterized in that: The activity index of the granulated blast furnace slag is greater than 95%, the particle size is 25-300 μm, and the calcium oxide content is greater than or equal to 40%; the activity index of the fly ash is greater than or equal to 50%, the particle size is 25-300 μm, and the aluminum oxide content is greater than or equal to 30%.

6. The method for preparing permeable bricks based on fly ash-based polymer artificial aggregate according to claim 1, characterized in that: The modulus of the water glass solution in step (1-1) is 1.3-1.5, and the solid content is 20-30%.

7. The method for preparing permeable bricks based on fly ash-based polymer artificial aggregate according to claim 1, characterized in that: The inorganic retarder is one or both of barium chloride and barium nitrate.

8. The method for preparing permeable bricks based on fly ash-based polymer artificial aggregate according to claim 7, characterized in that: The initial setting time of the slurry in step (1-2) is 30-90 minutes.

9. A permeable brick based on fly ash-based polymer artificial aggregate, characterized in that: The permeable brick is prepared by the preparation method of fly ash-based polymer artificial aggregate according to any one of claims 1 to 8.

10. A method for preparing a large amount of fly ash-based polymer artificial aggregate, characterized in that: The following steps are involved: (1-1) Ingredients: including powder ingredients and liquid ingredients; The powder ingredients are: fly ash and granulated blast furnace slag are weighed according to a weight ratio, wherein the fly ash content is 70-90%, and the granulated blast furnace slag content is 10-30%, and the powder materials are mixed evenly; The liquid ingredients include: weighing water, water glass and inorganic retarder according to weight ratio, wherein the water content is 15-30%, the water glass content is 60-85%, and the inorganic retarder content is 0.5-2%, and the liquid is mixed evenly; (1-2) Slurry preparation: Mix the powder material and the liquid material and stir for 5-15 minutes to prepare a uniform slurry; (1-3) Molding: Pour the slurry into the mold and vibrate for 5-10 seconds to make it dense; (1-4) Curing: After the slurry initially sets, steam curing or autoclave curing is used; (1-5) Processing: After curing, the solidified body is crushed and sieved by screening equipment to obtain fly ash-based polymer artificial aggregate with particle sizes of 2-5 mm and 5-10 mm.

Citation Information

Patent Citations

  • A method for preparing permeable bricks with high fly ash content

    CN110606720B

  • Coal ash-based ceramic water permeable brick sintered by two-step method and preparation method thereof

    CN111978096A

  • Method for preparing fly ash based ceramic water permeable brick by using pore forming agent method

    CN113292313A

  • Preparation method of high-volume fly ash-based water permeable brick

    CN110606720A

  • Rapidly-hardened high-strength fly ash geopolymer material and preparation method thereof

    CN113416025A